2022
DOI: 10.4081/ejtm.2022.10409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-acetylcysteine and metformin treatment on the stereopathological characteristics of uterus and ovary

Abstract: In this study, the stereo-pathological effect of metformin and N-acetyl cysteine is evaluated on the uterus and ovary of polycystic ovary syndrome (PCOS) mice. 96 mature females (8-weekold, weight of 20–30 gr) BALB/c mice were classified into 6 groups including the control group (n= 16), letrozole-induced PCOS group (n=16), PCOS + metformin (n=16), PCOS+NAC (n=16) and a separate control group for NAC (n=16). Another PCOS group was maintained for a month to make sure that features remain till the end of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…The paraffin block was then put on the θ -clock, and the division was performed along with the chosen score ( Figure 1(a) ) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The paraffin block was then put on the θ -clock, and the division was performed along with the chosen score ( Figure 1(a) ) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The volumes of the ovary were assessed by Cavalieri's principle [ 20 ]. For this purpose, 8–12 sections per rat were chosen by systematic random sampling.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on mares have shown that the administration of NAC can support the antibiotic treatment of endometritis by reducing inflammation [ 18 ]. Additionally, NAC exerts a positive effect on the treatment of polycystic ovary syndrome (PCOS) [ 19 ]; specifically, NAC improves the receptivity and decidualization of the rat uterus and the level of gene expression during placental differentiation and is beneficial for foetal survival [ 20 ]. In addition, NAC improves production performance, reproductive performance, antioxidant status, immunity, and the delivery of maternal antibodies in Japanese quail under heat stress conditions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%